Kajian Fiqh Wanita Dasar tentang Haid dan Hukum yang Berkaitan dengannya pada Siswi Mtss Tahfidzul Qur’an Al- Azzam - Jannah Lukman (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2022)
This community service aims to equip students with knowledge about menstruation and things that need to be considered as a consequence of menstruatruation. This dedication is carried out for the students of Islamic Elementary School Memorizing Qur’an Al-Azzam grades 1, 2 and 3. After this debriefing is given, it is hoped that the students will be more focused in doing worship and practicing it in daily life in accordance with the Sunnah that The Prophet Peace Be Upon Him taught through his Hadiths. Before carrying out this activity, the speaker coordinated in advance with the school to find out the expectations and conditions of the students. The activity included: the stages of opening; material explaination; question and answer; and closing statement.